Clinical utility of readily available novel markers of carotid atherosclerotic burden for reclassification and discrimination of very high cardiovascular risk. (14th October 2021) - Mavraganis, G; Georgiopoulos, G; Delialis, D; Aivalioti, E; Dimopoulou, A M; Sianis, A; Angelidakis, L; Patras, R; Petropoulos, I; Ioannou, S; Syrigou, R; Kanakakis, J; et al.
Abstract: Background: Among high cardiovascular (CV) risk patients, there is emerging need to recognize those who will benefit from new treatments targeting residual risk. Readily available modalities providing reclassification value would be clinically useful in this setting. Preliminary data suggest that carotid ultrasonography using plaque burden but not intima-media thickness (IMT) is associated with very high risk. Objectives: We aimed to assess the reclassification ability of two markers of carotid atherosclerosis in high-risk patients, reflecting total atherosclerotic burden and the most severe lesion and to compare them with the routinely used carotid indices IMT and number of carotid plaques. Methods: In an ongoing registry of patients who visited a cardiovascular protection clinic for cardiovascular risk assessment, we enrolled 735 consecutively recruited patients (mean age 63.1 years, 68.8% male) classified as high or very-high CV risk according to 2019 European Society of Cardiology /European Atherosclerosis Society Guidelines. Sum of carotid wall thickness (sumWT) and maximal wall thickness (maxWT) using high-resolution ultrasonography at baseline were used to assess the total burden and the most severe carotid lesion, respectively. These markers integrate maximum plaque height or maximum IMT if no plaque is present. All patients were followed for a median of 41 months and the primary end-point consisted of CV mortality, acute myocardial infarction or coronary revascularization. Results: After adjustment for traditional CV risk factors, maxWT and sumWT were associated with the primary end-point (hazard ratio [HR]=1.73 (95% confidence interval [CI]:1.39 to 2.17) and 1.19 (95% CI 1.10 to 1.30) respectively). Both markers were superior in terms of reclassification and discrimination to identify very high risk over validated CV risk scores including the Heartscore and the SMART score (net reclassification index [NRI]=0.624, p<0.0001, integrated discrimination index [IDI]=0.060, p<0.0001 and difference in the area under the curve (δAUC) = 0.136, p<0.001 for maxWT and NRI=0.497, p<0.0001, IDI=0.046, p<0.0001 and δAUC = 0.128, p<0.001 for sumWT), IMT (NRI=0.502, p<0.0001, IDI= 0.058, p=0.02 for maxWT and NRI=0.559, p<0.0001, IDI=0.051, p=0.016 for sumWT) and the number of carotid plaques (NRI=0.614, p<0.0001, IDI=0.038, p=0.001 for maxWT and NRI=0.292, p=0.019, IDI=0.022, p=0.009 for sumWT). Conclusions: The use of two novel cumulative markers of atherosclerotic burden improves risk stratification and discriminates high from very high CV risk. Given that carotid ultrasonography is a readily available modality, its clinical application for risk refinement of high-risk patients to facilitate treatment decisions merits further investigation. FUNDunding Acknowledgement: Type of funding sources: None.